"A smartphone made my life easier": An exploratory study on age of adolescent smartphone acquisition and well-being. (January 2021) - Vaterlaus, J. Mitchell; Aylward, Alexandra; Tarabochia, Dawn; Martin, Jillian D.
Abstract: Most adolescents in the United States have access to a smartphone. The appropriate timing of smartphone acquisition during adolescence has not been empirically determined. The current study included a diverse sample of 686 late adolescent (18–25 years old; n  = 352 female) participants who acquired their smartphones in early (15.45%), middle (60.64%), and late (23.91%) adolescence. Multiple linear regression models were used to determine if age of smartphone acquisition was predictive of well-being outcomes in later adolescence. Results indicated that age of smartphone acquisition was largely not predictive of later well-being (i.e., depression, loneliness, life satisfaction, interpersonal communication, cell phone addiction). A qualitative content analysis approach was used to identify the participants' experiences with smartphone acquisition during adolescence. Three themes were identified: development and growth, parents: gatekeepers to acquisition, and smartphones necessary for adolescent access. Results suggest that parents, maturity, and responsibility may be more important in determining timing of smartphone acquisition, rather than a specific age. Highlights: Age of smartphone acquisition largely does not predict well-being in later adolescence. Parents perceived as the people who should determine adolescent smartphone readiness. Preventing adolescent access to a smartphone thought to have negative social outcomes.